An Introduction to Rights / [electronic resource] - Edmundson, William A. (Cambridge : Cambridge University Press, 2012)
An Introduction to Rights is a readable and accessible introduction to the history, logic, moral implications and political tendencies of the idea of rights. It is organized chronologically and discusses important historical events such as the French and American Revolutions. It treats a range of historical figures, including Grotius, Paley, Hobbes, Locke, Bentham, Burke, Godwin, Douglass, Mill and Hohfeld and relates the concept of rights to contemporary debates such as consequentialism versus contractualism. This thoroughly updated second edition includes a new preface and expands the discussion of the surprising role that slavery has played in the history of rights. It includes new material on egalitarianism, distributive justice and what the demand for equal rights means.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Civil rights; Human rights